Plasmonic gold nanoparticles aggregate based on charge neutralization for the convenient detection of fumonisin B1 by colorimetry and SERS. (May 2023) - Xing, Keyu; Bao, Huanhuan; Ding, Nengshui; Xiong, Yonghua; Peng, Juan; Lai, Weihua
Abstract: A novel charge neutralization strategy with positively charged SYBR Green I was used for the convenient detection of fumonisin B1. In the absence of the fumonisin B1, the aggregation of gold nanoparticles would appear in less than 2 min. In the presence of the fumonisin B1, the positive charge of SYBR Green I was neutralized by the negatively charged fumonisin B1. As a result, the aggregation of gold nanoparticles could not be achieved. Based on the charge neutralization strategy, the colorimetry and surface enhanced Raman spectroscopy (SERS) dual-channel methods were developed for the detection of fumonisin B1 in corn. The naked eye sensitivity was 500 μg kg −1 in the colorimetric method. The limit of detection was 54.86 μg kg −1 in the SERS method. The developed methods had a high stability (coefficient of variation <8.3%). Graphical abstract: Image 1 Highlights: AuNPs aggregate could be rapidly formed by the positive charge of SG. The positive charge of SG could be neutralized by the negative charge of FB1. Colorimetric method was developed for the convenient detection of FB1. SERS method was developed for the quantitative detection of FB1.